2016
DOI: 10.1002/smi.2693
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Demands of Schooling, Stress and Mental Health: Changes from Grade 6 to Grade 9 as a Function of Gender and Cognitive Ability

Abstract: The link between perceived demands of school, stress and mental health in relation to gender is complex. The study examined, with two waves of longitudinal data at age 13 and age 16, how changes in perceived academic demands relate to changes in perceived stress, taking into account gender and cognitive ability, and to investigate how these factors affect the level of psychosomatic and depressive symptoms at the age of 16. A nationally representative sample including about 9000 individuals from the Swedish lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 43 publications
6
52
0
Order By: Relevance
“…Despite results obtained in relation to the first objective have not shown significant gender differences, average marks on stress perception have been higher in female subjects than in male. Like previous studies [31], no differences have been found in stress perception according to gender. Following the line of study focused on perfectionism in students [10], it is affirmed that there are no gender differences in terms of perfectionism indicators.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Despite results obtained in relation to the first objective have not shown significant gender differences, average marks on stress perception have been higher in female subjects than in male. Like previous studies [31], no differences have been found in stress perception according to gender. Following the line of study focused on perfectionism in students [10], it is affirmed that there are no gender differences in terms of perfectionism indicators.…”
Section: Discussionsupporting
confidence: 68%
“…Until some decades ago perfectionism was understood as dysfunctional, being related to eating disorders [43,45], anxiety and depression [32], and stress [31,33]. Previous studies starting from this perspective have tried to explain perfectionism without understanding potential factors that can serve as emotional resources to withstand stress [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gecková et al 2003;Giota and Gustafsson 2016;Wiklund and Wiklund-Fjellman 2013;Wiklund et al 2012). Findings from the current study reveal that it has become more common for young people to selfmedicate, by using drugs and pills to 'handle' their problems, regardless of whether these problems are related to domestic violence or something else.…”
Section: Discussionmentioning
confidence: 67%
“…The issue of not being believed could mirror the perception that today's young people may be regarded as less sturdy than previous generations [46,47]. Research has revealed the increasing pressure on today's adolescents with greater stress physically, socially, and emotionally [48]. This factor could be used against AYAs with persistent pain so that their subjective experience is not acknowledged.…”
Section: Juggling Pain With Everyday Lifementioning
confidence: 99%